Denial : the final stage of genocide - Cox, John M. 1963- HerausgeberIn; Khoury, Amal HerausgeberIn; Minslow, Sarah 1982- HerausgeberIn (Routledge, 2022)
Is denial the final stage? Consolidation and the metaphysical dimensions of denial / Henry C. Theriault -- Holomodor and Holocaust memory in competition and cooperation / Kristen Dyck -- Denial and the Duvalier regime in Haiti / Jean-Philippe Belleau -- The Soviet denial of murdered Jews' identity during and after the great patriotic war / Thomas Earl Porter -- Commemorating seventeenth-century Dutch colonial violence / Mark Meuwese -- Triumphalism: the final stage of Bosnian genocide / Hikmet Karčić -- The Bosnian genocide and the "continuum of denial" / Simon Massey -- Beyond erasure: indigenous Genocide denial and settler colonialism / Michelle A. Stanley -- Denying Rwanda, denying Congo / Adam Jones -- Reclaiming the denied genocide victim identity through music / Margarita Tadevosyan -- Gendercide in the twenty-first century and the destruction of the transgender body / Haley Marie Brown -- Toward trauma-informed transitional justice praxis / Jeremy A. Rinker.